Odpowiedzi

2010-02-23T13:10:21+01:00
A)
2b-(b+2a+1) =
= 2b - b - 2a - 1 =
= b - 2a - 1

b)
(2a-3b)-(4a-5b) =
= 2a - 3b - 4a + 5b =
= -2a + 2b

c)
-8(-3-7y+2x) =
= 24 + 56y - 16x

d)
5x²(x³+3x-1) =
= 5x⁵ + 15x³ - 5x²
  • Użytkownik Zadane
2010-02-23T13:11:13+01:00
A) 2b-b-2a-1=b-2a-1
b) 2a-3b-4a+5b=2b-2a
c) 24+56b-16a
d) 5x^5+15x^3-5x^2
Najlepsza Odpowiedź!
2010-02-23T13:12:26+01:00
2b-(b+2a+1)= 2b-b-2a-1 = b-2a-1

(2a-3b)-(4a-5b)=2a-3b-4a+5b= -2a+2b

-8(-3-7y+2x)=24+56y-16x

5x²(x³+3x-1)=5x⁵+15x³-5x²